Save Yourself - Esposito, Cameron (Grand Central Publishing, 2020)
This "hilarious and honest" bestselling memoir from a rising comedy star tackles issues of gender, sexuality, feminism, and the Catholic childhood that prepared her for a career as an outspoken lesbian comedian (Abby Wambach).Cameron Esposito wanted to be a priest and ended up a stand-up comic. Now she would like to tell the whole queer as hell story. Her story. Not the sidebar to a straight person's rebirth-she doesn't give a makeover or plan a wedding or get a couple back together. This isn't a queer tragedy. She doesn't die at the end of this book, having finally decided to kiss the girl. It's the sexy, honest, bumpy, and triumphant dyke's tale her younger, wasn't-allowed-to-watch-Ellen self needed to read. Because there was a long time when she thought she wouldn't make it. Not as a comic, but as a human. SAVE YOURSELF is full of funny and insightful recollections about everything from coming out (at a Catholic college where sexual orientation wasn't in the nondiscrimination policy) to how joining the circus can help you become a better comic (so much nudity) to accepting yourself for who you are-even if you're, say, a bowl cut-sporting, bespectacled, gender-nonconforming child with an eye patch (which Cameron was). Packed with heart, humor, and cringeworthy stories anyone who has gone through puberty, fallen in love, started a career, or had period sex in Rome can relate to, Cameron's memoir is for that timid, fenced-in kid in all of us-and the fearless stand-up yearning to break free.
Keywords: amériques; approches et analyses; corps; humour; identités LGBTQIA2+; personnes lesbiennes; privilèges; régions géographiques; sexisme; sexualité; systèmes d'oppression; thématiques; travail; états-unis

Postures et privilèges - Institut de recherches et d'études féministes (FéminÉtudes, 2016)
Ce nouveau format de publication tend vers le livre d’artistes et illustres autant les postures féministes que ces privilèges. Postures & Privilèges, voilà un thème qui s’impose. Parce que les oppressions sont multiples; parce que les féminismes sont pluriels. Parce que les luttes tirent précisément leur force et leur vitalité de cette diversité d’expériences, de points de vue et de positionnements théoriques dans lesquels chaque féministe se construit. Et parce qu’en étant plurielles, on peut être allié.e.s et solidaires, veut-on espérer. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000-2029; 2010-2019; amériques; approches et analyses; corps; création; cyberféminisme; féminétudes; identités LGBTQIA2+; identités de genre; justice sociale; maternité; militance; privilèges; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppression; thématiques; trans; violences; violences contre les femmes*; écriture des femmes*

Moving toward the ugly: A politic beyond desirability - Mingus, Mia (Leaving Evidence, 2011)
*Femmes Of Color Symposium Keynote Speech, Oakland, CA (8/21/11)
Keywords: approches et analyses; capacitisme; corps; discours dominant; fem3100; identités LGBTQIA2+; identités de genre; premier cycle; privilèges; queer; racisme; ressource en ligne; sexisme; sexualité; systèmes d'oppression; thématiques